Detection of E coli from wildlife in disturbed and undisturbed habitats in Sarawak, Malaysian Borneo - Kasing, Apun; YEE LING, Chong; F. H. H, Hashimatul; Mustafa, Abdul rahman; Lesley Maurice, Bilung (Researchgate Publisher, 2011)
his study was conducted to screen E.coli from bats, rodents and chicken in Sarawak, Malaysian Borneo.